Archival Interventions and Disentangling Legacy Records - Cook, Sarah (Archivaria)

(untitled) (Association of Canadian Archivists, 2021)
Appraisal and disposition of government records at Library and Archives Canada (LAC) focuses primarily on acquiring the “right” records to best document a given function of the Government of Canada. Once records pass into LAC’s care, access is provided through an inconsistent approach of online descriptive records and on-site finding aids, often with minimal or incorrect contextualizing information that hinders their overall discoverability and use. Through a study of both the legacy photographic records in the National Film Board of Canada Fonds and the recontextualization project currently underway at LAC, the author examines the history of the record, from recordkeeping practices to the transfer to LAC, and some of the interventions by the archives to describe and shape these records over several generations of custodial care. All of these various actions have had a hidden impact on the use and understanding of both the individual records and the larger collection. This article provides a case study in how rearrangement based on research into creators, organizational recordkeeping systems, and archival custodial practices can draw out complex, multiple provenances and provide researchers with a fuller contextual history of the record.